LncRNA-H19 Drives Cardiomyocyte Senescence by Targeting miR-19a/socs1/p53 Axis - Zhuang, Yuting; Li, Tingting; Xiao, Hongwen; Wu, Jiaxu; Su, Shuang; Dong, Xue; Hu, Xiaoxi; Hua, Qi; Liu, Junwu; Shang, Wendi; Ju, Jiaming; Sun, Fei; et al. (Frontiers in Pharmacology, 2021)
Purpose: Cardiomyocyte senescence is associated with a progressive decline in cardiac physiological function and the risk of cardiovascular events. lncRNA H19 (H19), a well-known long noncoding RNA (lncRNA), is involved in the pathophysiological process of multiple cardiovascular disease such as heart failure, cardiac ischemia and fibrosis. However, the role of H19 in cardiomyocyte senescence remains to be further explored. Methods: Senescence-associated β-galactosidases (SA-β-gal) staining and acridine orange/ethidium bromide fluorescence staining were used to detect cardiomyocyte senescence. Western blot, qRT-PCR and luciferase reporter assay were employed to evaluate the role of H19 in cardiomyocyte senescence and its underling molecular mechanism. Results: H19 level was significantly increased in high glucose-induced senescence cardiomyocytes and aged mouse hearts. Overexpression of H19 enhanced the number of SA-β-gal-positive cells, and the expression of senescence-related proteins p53 and p21, whereas H19 knockdown exerted the opposite effects. Mechanistically, H19 was demonstrated as a competing endogenous RNA (ceRNA) for microRNA-19a (miR-19a); H19 overexpression downregulated miR-19a level, while H19 knockdown upregulated miR-19a. The expression of SOSCI was dramatically increased in senescence cardiomyocytes and aged mouse hearts. Further experiments identified SOCS1 as a downstream target of miR-19a. H19 upregulated SOCS1 expression and activated the p53/p21 pathway by targeting miR-19a, thus promoting the cardiomyocytes senescence. Conclusion: Our results show that H19 is a pro-senescence lncRNA in cardiomyocytes acting as a ceRNA to target the miR-19a/SOCS1/p53/p21 pathway. Our research reveals a molecular mechanism of cardiomyocyte senescence regulation, and provides a novel target of the therapy for senescence-associated cardiac diseases.